Assessment the Water Supply System of Qom City Based on the Water Safety Plan - Sanaz Nozariamini; Sara Miryousefi Ata; Bakhrul Khair Amal (Britain International for Academic Research (BIAR) Publisher, 2020)
The existing condition of potable water in the city of Qom and its adjacent villages needs improvement, both for the quantity as well as the quality. On one side, the excess use of wells has decreased the level of underground water, resulting to Penetration of salty water from the neighboring salt lake into the underground water and therefore, lowering the quality of potable water, and on the other side, during the recent years the consumption of water has increased due to growth of the city population. Because of these factors, the improvement of quality and overcoming the shortage of drinkable water in the city of Qom and its adjacent villages, have turned to an urgent need. To respond to the above-mentioned needs, some studies have been carried out by a number of consultants during the past years. In addition, based on such studies, certain projects have been implemented to provide new sources of potable water for the city of Qom.this paper aims at investigating the existing condition of potable water in the city of Qom. The goal of this water treatment is to supply the drinkable water for agriculture and industry and producing the energy.